ChemInform Abstract: Polypeptide Films via N‐Carboxyanhydride Ring‐Opening Polymerization (NCA‐ROP): Past, Present and Future. Issue 27 (8th July 2014) - Wibowo, Steven Harris; Sulistio, Adrian; Wong, Edgar H. H.; Blencowe, Anton; Qiao, Greg G.
Abstract Review: 101 refs.